Analisa Desain dan Kalkulasi Biaya Pembangunan Kapal Perikanan 5 GT Berbahan Fiberglass untuk Perairan Riau - Romadhoni Romadhoni; Budhi Santoso; Sidik Purwoko; Polaris Nasution (IPM2KPE, 2023)
This study aims to design a fiberglass vessel with a capacity of 5 GT, the standard for the Indonesian BKI classification bureau, which is a reference in the capture fisheries development program in Riau province. This research method uses field survey methods and interviews with ship owners in determining the main size, software simulation in determining resistance and power values, and economic calculations and material requirements are carried out when building ships in the shipyard. The results of this study resulted in a 5 GT fishing boat design according to the Indonesian Classification Agency (BKI) FRP Fishing Boat Less than 12 M. The main dimensions of a 5 GT fishing boat are 12.5 m long, 2.6 m wide, 1.2 m high, 0 draft. .6 m, then the results of the simulation on the maxsuft resistance software obtained the results of a resistance of 4.3 kN at a speed of 12 knots so that an engine power of 48 HP was obtained. Furthermore, the estimated cost of making and fabricating fiberglass vessels in the field is IDR 445,864,800 including VAT. In conclusion, the results of the calculation of the cost component and the fabrication of a fishing vessel with a capacity of 5 GT is Rp. 445,864,800 (Four hundred Forty Five Million Eight Hundred Sixty Four Thousand Eight Hundred Rupiah) including 11% value added tax. Keywords: Fiberglass Cost, Design, Fabrication, Fishing Ship